DRUG RELATED PROBLEMS EVALUATION OF CHRONIC KIDNEY DISEASE PATIENTS IN INPATIENT DEPARTMENT OF FATMAWATI GENERAL HOSPITAL - Lusi Indriani; Anton Bahtiar; Retnosari Andrajati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The use of drugs in patients with decreased renal function allows the occurrence of drug related problems. Pharmacist has responsibility to identify and to prevent drug related problems. This study was proposed to evaluate drug related problems in chronic kidney disease patients in Inpatient Department of Fatmawati General Hospital. It was descriptive analitic study with prospectively approach. The primary data was obtained by identifying drug related problems. The secondary data was taken from medical record of chronic kidney disease patients such as: age, sex, the stage of chronic kidney disease, comorbidity, and drug therapy. This study took place in Inpatient Department of Fatmawati General Hospital during the period of January to March 2012. Univariate analysis had done to obtain description of frequency and proportion of research variables such as the patient characteristics who received drug therapy (age, sex, the stage of chronic kidney disease, and comorbidity), the drug therapy characterictics that evaluated based on the number and type of drug therapy and drug related problems. Bivariate analysis of the Spearman correlation test was taken to evaluate whether there was correlation beetwen confounding variables and incident of drug related problems. The evaluation was taken in 40 chronic kidney disease patients with 377 number of drugs. The number of drug related problems was 98 issues (25.99% of prescribing drugs). Type of drug related problems were not optimal effect of drug treatments 62.24%, the incidence of non-allergic adverse drug events 20.41%, and the incidence of toxic adverse drug-events 17.35%. The confounding variables that significantly influence the incidence of drug related problems were comorbidities (r= 0.385; p= 0.014), and the number of drugs (r= 0.604; p= 0.000).Keywords: drug related problems, chronic kidney disease, Fatmawati General Hospital